Management and disclosure of quality issues in forensic science: A survey of current practice in Australia and New Zealand - Heavey, Anna; Turbett, Gavin; Houck, Max; Lewis, Simon (2023)
The investigation of quality issues detected within the forensic process is a critical feature in robust quality management systems to provide assurance of the validity of reported results and inform strategies for continuous improvement and innovation. A survey was conducted to gain insight into the current state of practice in the management and handling of quality issues amongst the government service provider agencies of Australia and New Zealand. The results demonstrate the value of standardised quality system structures for the recording and management of quality issues, but also areas where inconsistent reporting increases the risk of overlooking important data to inform continuous improvement. With new international changes requiring mandatory reporting of quality issues, this highlights compliance challenges that agencies will face. This study reinforces the need for further research into the standardisation of systems underpinning the management of quality issues in forensic science to support transparent and reliable justice outcomes.